Introduction to international economic law - Palombino, Fulvio Maria; Rossi, Pierfrancesco (Routledge, Taylor & Francis Group, 2025)
International Economic Law (IEL) refers to the rules governing economic relations at the international level and involving States, international organizations and private entities. This textbook explores IEL within the broader context of public international law from the ground up, providing all the foundational principles of international law essential for the study of IEL. The first part of the book is devoted to the analysis of actors and sources of IEL while the second part focuses on the three main sectors of IEL: international investment law, the law of international trade, as developed through the work of the World Trade Organization (WTO), and international financial and monetary law. Through references to conventional rules, landmark cases and decisions of international organizations, Introduction to International Economic Law provides a clear and concise primer on the main issues in current IEL. It will be an ideal textbook for students taking introductory courses in IEL, as well as a useful guide for anyone wishing to learn about the subject and understand the dynamics behind it.
Keywords: Commercial law.; Public international law; International economic law; World Trade Organization; International investment law; Investment arbitration; International development; International financial institutions; International trade law; elektronické knihy; electronic books